2014
DOI: 10.1111/tmi.12278
|View full text |Cite
|
Sign up to set email alerts
|

Four‐year retention and risk factors for attrition among members of community ART groups in Tete, Mozambique

Abstract: Abstractobjective Community ART groups (CAG), peer support groups involved in community ART distribution and mutual psychosocial support, were piloted to respond to staggering antiretroviral treatment (ART) attrition in Mozambique. To understand the impact of CAG on long-term retention, we estimated mortality and lost-to-follow-up (LTFU) rates and assessed predictors for attrition.methods Retrospective cohort study. Kaplan-Meier techniques were used to estimate mortality and LTFU in CAG. Individual-and CAG-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(143 citation statements)
references
References 18 publications
5
136
1
1
Order By: Relevance
“…If a patient had no money, he would not go to the clinic, that is why there were many deaths. Now the number of deaths decreased because with the groups, we are helping each other [65].^Furthermore, observational analyses of CAG cohorts (n = 5729) demonstrated 4-year retention rates of greater than 90 % in Mozambique [63]. Thus, CAGs represent a promising intervention that can address multiple barriers (structural, clinical, and psychosocial) at the same time.…”
Section: Cross-cutting Interventionsmentioning
confidence: 95%
See 1 more Smart Citation
“…If a patient had no money, he would not go to the clinic, that is why there were many deaths. Now the number of deaths decreased because with the groups, we are helping each other [65].^Furthermore, observational analyses of CAG cohorts (n = 5729) demonstrated 4-year retention rates of greater than 90 % in Mozambique [63]. Thus, CAGs represent a promising intervention that can address multiple barriers (structural, clinical, and psychosocial) at the same time.…”
Section: Cross-cutting Interventionsmentioning
confidence: 95%
“…In CAGs, groups of six stable HIV patients meet in the community and take a greater role in managing their own illness by taking turns obtaining medications from the clinic for the entire group, self-monitoring medication adherence, and providing support to each other [62][63][64]. By working together, a group of patients transfers the ownership of the treatment process into the community thereby enhancing patient activation, social normalization, and routinization simultaneously.…”
Section: Cross-cutting Interventionsmentioning
confidence: 97%
“…9 In the same project a qualitative study showed that peer support resulted in a better understanding of treatment, improved adherence and retention on ART. Moreover, the group dynamic created a protective environment where patients discuss problems, exchange experiences and support each other.…”
Section: Discussionmentioning
confidence: 99%
“…6 Scale-up of ART has been hampered by chronic understaffing and inadequate infrastructure in the healthcare system. 7 In 2009, drawing on a care model rolled out in Mozambique, 8,9 the Lesotho Ministry of Health decided to pilot Community ART Groups (CAG). CAG are self-formed peer groups, in which PLWHA engage to assure community ART distribution.…”
Section: Introductionmentioning
confidence: 99%
“…CAGs have been shown to decongest busy clinics by reducing the number of individual patient visits and improving long-term retention in Mozambique. 23 How these differentiated care strategies improve the quality of the service for the patient (shorter waiting times, less money spent on travel, peer support) and encourage self-management is also worth evaluating.…”
Section: Public Health Actionmentioning
confidence: 99%